The Effect Murottal Qur'an on The Sleep Quality of Babies Aged 3-6 Months at The Yonkav 8 Tank Clinic Beji - Ika Nuraini; Reny Retnaningsih; Rosyidah Alfitri (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2024)
Introduction: At the age of 3-6 months, the baby's total sleep time is around 13-15 hours/day, and babies aged 3-6 months usually tend to have irregular sleep duration. Good quality sleep in babies affects not only the baby's intelligence and brain development but also the baby's attitude when he wakes up. Al-Quran murrotal treatment is a useful tool for treating sleep issues in infants. Our auditory organs receive Murottal Qur'an therapy, which is subsequently sent to the limbic system, a region of the brain in the middle of the brain that controls hormones in developing children. Material and Methods: Pre-experimental methodology with a single group pretest-posttest design is used in this kind of study. Purposive sampling was used to choose 16 infants, ages 3-6 months, from the Federer formula. Results: Comprised of sixteen infants who had poor sleep quality. Following murottal qur'an therapy, 15 babies (93.8%) were able to sleep through the night, while one baby (6.2%) continued to have issues with the quality of their sleep. The Wilcoxon test research yielded a p-value of 0.000, indicating that there is a significant effect of delivering murottal Al-Qur'an therapy on the quality of a baby's sleep (p < 0.005). Conclusion: There is an effect of providing murottal Al-Qur'an therapy on the sleep duration of babies aged 3-6 months.